(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
Mental health is essential for human, social and community development; furthermore, it is a right for everyone. Reflecting on mental health and strategies to promote it is not only important, but a current urgency, evident in the face of the high rates of psychological and emotional illnesses. In accordance with the above, a theoretical review with an exploratory and descriptive scope accompanied by professional reflections is established in this text. It highlights -within its results- mental health as possible as long as social factors among other socio-dynamic and community aspects, including political, structural and socioeconomic ones are taken into consideration. Recognizing the imminent need for an adequate and energetic promotion of mental health, it must be made visible that this is not limited to the individual efforts made to achieve it; mental health, rather, is constructed and enhanced at the community level and through social and group interaction. Mental health is a social, political and structural issue as well as an individual one.